PLAČEVANJE V SPLETNIH TRGOVINAH S POUDARKOM NA PLAČILNIH KARTICAH IN PAYPALU - Kotnik, Natalija (N. Kotnik, 2009)
Živimo v svetu novosti, inovacij in sprememb. Največje spremembe prihajajo v povezavi s tehniko, računalniki in internetom. Vsa podjetja spreminjajo del, če ne celotno svoje poslovanje v elektronsko obliko in čedalje več vsakodnevnih opravil se opravlja preko elektronskih medijev. Tako je tudi s spletnim nakupovanjem, ki se je v bolj razvitem svetu že dodobra razvilo, pri nas pa šele prihaja v razvito. Ker ima dovolj prednosti nasproti navadnega, klasičnega nakupovanja, bo sčasoma še bolj prisotno v našem življenju, če ne nepogrešljivo. Internet postaja vse bolj pomembno nakupno mesto in kreditna kartica je najbolj uveljavljeno plačilno sredstvo v njem. Najbolj razširjeni sta Visa in Eurocard/Mastercard. V prvem delu diplomske naloge sem na kratko opisala spletne trgovine. V nadaljevanju pa sem se opredelila na možne načine plačila preko spleta, kot so: Moneta, PayPal, Plačilne kartice. Pri plačilnih karticah sem vzpostavila njihove značilnosti, prednosti in slabosti. Njihov potek pri plačevanju preko spleta, varnost. Naredila sem tudi raziskavo uporabe kartic pri različnih bankah. Na kratko sem predstavila tudi Moneto. PayPal kot najmanj znano plačilno sredstvo pri naših spletnih trgovcih, mi je delal malo več težav, saj sem morala dosti več iskati sama po internetu in literaturi, ki je pa ni bilo dosti. Opisala sem njegove prednosti in slabosti, postopek pri plačilu, njegovo varnost in raziskala primer podjetja Vitapur. Najpogostejši razlogi, ki odvračajo ljudi od e-nakupovanja in hkrati uporabe elektronskih plačilnih sistemov so: nevarnost zlorabe kreditne kartice, zloraba osebnih podatkov in nezaupljivost do e-trgovcev. Prednosti e-trgovine za kupca so predvsem prihranek v času, izogibanje gneči in nakup od doma. Lastnosti kvalitetne spletne trgovine so: zagotovilo, da osebe nakupujejo preko varne povezave, preprosto sprehajanje po spletni trgovini in tajnost podatkov kupca. Večina predstavljenih elektronskih plačilnih sistemov ni nikoli doživela množične, globalne uporabe. Predvsem gre razloge za to iskati v prezapletenosti sistemov, nekompatibilnosti strojne in programske opreme, stroških njihove uporabe in še vedno prisotnem nezaupanju ljudi, da bi kupovali preko svetovnega spleta. Uspešni so le tisti sistemi, ki so našli dovolj dober kompromis med varnostjo in prijaznostjo do uporabnika. Z razvojem tehnologije narašča zaščita in varnost zasebnosti na internetu. Zelo pomembno je, da kupci v e-trgovinah varujejo svoje podatke in jih ne posredujejo preko nezavarovanih mehanizmov, saj tako sami pripomorejo k zlorabam. V svetu hitrega tehnološkega razvoja bodo preživeli le tisti, ki bodo znali izkoristiti priložnosti, ki jih ponuja ekonomija. We live in a world of novelty, innovation and change. The biggest changes emerge in correlation with technology, computers and the Internet. All companies are changing a part of if not all its operations into an electronic form and more and more everyday tasks are carried out through electronic media. This is also the case with online shopping that has greatly developed in the developed world but in our country it is yet to come so. Since it has enough advantages compared to the ordinary, conventional shopping, it will become even more present in our lives if not indispensable. Internet is becoming increasingly important as a place of purchase and credit card is the most established mean of payment in it. The most common credit cards are Visa and Eurocard / Mastercard. In the first part of the graduation thesis I focused on online shops, types of online shops and their advantages and disadvantages. When writing the thesis I also stated and described reasons why some people still refuse to buy online. I also described the safety of shopping on the Internet, its structure and the purchase process. Then I defined possible payment modes via the Internet such as: Moneta, PayPal, credit cards. With payment cards I established their characteristics, advantages and disadvantages, their course when paying online and security. I carried out a survey of credit cards use in different banks. With Moneta I described its advantages and disadvantages, payment channels with a focus on Internet Moneta, the payment procedure and its safety. PayPal as a least known payment method with our online traders gave me a little more difficulties because I had to do much more Internet and literature research myself but there was not much available. I described its advantages and disadvantages, payment process, its safety and studied it on a case of Company Vitapur. The most common reasons that discourage people from e-shopping and of electronic payment systems are: the risk of credit card misuse, personal data misuse and distrust in e-retailers. Benefits of e-commerce for the customer are primarily time saving, avoiding crowds and buying from home. Characteristics of high-quality online shops are: ensuring that people shop via a secure connection, simple browsing through an online shop and buyer data confidentiality. Most of the presented electronic payment systems have never experienced a massive, global application. Primarily the reasons are found in complicated systems, hardware and software incompatibility, costs of its use and in still present distrust of people to buy via the Internet. Successful systems are only those that have found a sufficiently good compromise between security and user friendliness. With technological progress safety and protection of privacy on the Internet is increasing. It is very important for customers in e-shops to protect their information and do not transmit it via unsecured mechanisms which can lead to information abuse. In a world of rapid technological development only those who know how to exploit the opportunities offered by the economy will survive. ABSTRACT We live in a world of novelty, innovation and change. The biggest changes emerge in correlation with technology, computers and the Internet. All companies are changing a part of if not all its operations into an electronic form and more and more everyday tasks are carried out through electronic media. This is also the case with online shopping that has greatly developed in the developed world but in our country it is yet to come so. Since it has enough advantages compared to the ordinary, conventional shopping, it will become even more present in our lives if not indispensable. Internet is becoming increasingly important as a place of purchase and credit card is the most established mean of payment in it. The most common credit cards are Visa and Eurocard / Mastercard. In the first part of the graduation thesis I focused on online shops, types of online shops and their advantages a